A fractionally integrated exponential model for UK unemployment - Luis A. Gil-Ala\~na (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
Fractionally integrated models with the disturbances following a Bloomfield (1973) exponential spectral model are proposed in this article for modelling the U.K. unemployment. This enables us a better understanding of the low-frequency dynamics affecting the series, without relying on any particular ARMA specification for its short-run components, which, in general, requires many more parameters to estimate. The results indicate that this exponential model, confounded with fractional integration, may be a feasible way of modelling unemployment, also showing that its order of integration is much higher than one and thus, leading to the conclusion that the standard practice of taking first differences may lead to erroneous results.
urn:nbn:de:kobv:11-10047937
Keywords: C22; 330; long memory; unemployment; fractional integration